PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL DALAM MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA SISWA SEKOLAH DASAR - Khoiriyah, Dea Aminatul; Taufik, Taufik; Adi, Nur Romdlon Maslahul; Agustina, Yayuk (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to analyze the use of Wordwall as an interactive learning media in improving Indonesian language learning outcomes among third-grade elementary students. The research employed a descriptive qualitative approach focusing on the process and impact of Wordwall implementation in classroom learning. The participants included third-grade students and an Indonesian language teacher. Data were collected through observation sheets, interview guidelines, and assessment documents. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicated that the use of Wordwall increased students’ motivation and participation in learning. Interview data revealed improvements in students’ learning behavior, particularly in terms of activeness, cooperation, and enthusiasm during the learning process. Wordwall also helped simplify complex materials, such as direct and indirect sentences, through engaging game-based quizzes. Furthermore, the media supported differentiated learning by accommodating various learning styles, including visual, auditory, and kinesthetic. In conclusion, Wordwall is effective in creating an interactive, inclusive, and student-centered learning environment aligned with the principles of the Merdeka Curriculum.